Neutrophil to lymphocyte ratio as a predictor of response to neoadjuvant chemotherapy and survival in oesophageal adenocarcinoma. Issue 3 (31st March 2020) - Powell, A G M T; Chin, C; Coxon, A H; Chalishazar, A; Christian, A; Roberts, S A; Lewis, W G
Abstract: Background: Inflammation has an important role in cancer survival, yet whether serum markers of inflammation predict response to potentially curative neoadjuvant chemotherapy (NAC) in oesophageal adenocarcinoma (OAC) is controversial. This study aimed to determine whether the systemic inflammatory response (SIR) is associated with response to NAC and survival. Methods: Consecutive patients with OAC planned for surgery with curative intent received blood neutrophil and lymphocyte measurements at diagnosis to calculate the neutrophil to lymphocyte ratio (NLR). Pathological variables including pTNM stage, differentiation, vascular invasion and Mandard tumour regression grade (TRG) were recorded. TRGs 1 and 2 were taken to represent a good response, and the primary outcome was overall survival. Results: During follow-up of 136 patients, 36 patients (26·5 per cent) had recurrence and 69 (50·7 per cent) died. Receiver operating characteristic (ROC) curve analysis of NLR before NAC predicted poor TRG (area under the ROC curve 0·71, 95 per cent c.i. 0·58 to 0·83; P = 0·002). In univariable analysis, pT category ( P < 0·001), pN category ( P < 0·001), poor differentiation ( P = 0·006), margin positivity ( P = 0·001), poor TRG ( P = 0·014) and NLR (dichotomized at 2·25; P = 0·017) were associated with poor overall survival, and NLR retained independent significance in multivariable analysis (hazard ratio 2·26, 95 per cent c.i. 1·03 to 4·93; P = 0·042). Conclusion: The pretreatment NLR was associated with a pathological response to NAC and overall survival in patients with OAC. Antecedentes: La inflamación juega un importante papel en la supervivencia por cáncer, aunque aún no se sabe si los marcadores séricos de inflamación predicen la respuesta a la quimioterapia neoadyuvante ( neoadjuvant chemotherapy, NAC) potencialmente curativa en el adenocarcinoma de esófago ( oesophageal adenocarcinom a, OAC). Este estudio se propuso determinar si la respuesta inflamatoria sistémica ( systemic inflammatory response, SIR) estaba asociada con la respuesta a la NAC y a la supervivencia. Métodos: A pacientes consecutivos con OAC en los que se planificó cirugía con intención curativa se les determinó neutrófilos y linfocitos en sangre en el momento del diagnóstico para calcular la tasa neutrófilo-linfocito ( neutrophil-lymphocyte ratio, NLR). Se registraron variables patológicas que incluían el estadio pTNM, diferenciación tumoral, invasión vascular y grado de regresión tumoral ( tumour regression grade, TRG) de Mandard. Los grados TRG 1 y 2 fueron considerados como una buena respuesta y el resultado primario fue la supervivencia global ( overall survival, OS). Resultados: Durante el seguimiento de 136 pacientes, 36 pacientes (26, 5%) presentaron recidiva y 69 pacientes (50, 7%) fallecieron. El análisis de las características operativas del receptor ( receiver-operator-characteristic, ROC) de NLR antes de la NAC predijo una pobre TRG (área bajo la curva ROC, AUC 0, 71, i.c. del 95% 0, 58-0, 83, P = 0, 002). En el análisis univariable, el estadio pT ( P < 0, 001), el estadio pN ( P < 0, 001), una pobre diferenciación tumoral ( P = 0, 006), un margen positivo ( P = 0, 001), una pobre TRG ( P = 0, 014) y la NLR (dicotomizada a 2, 25, P = 0, 017) se asociaron con una pobre OS, pero solamente la NLR (cociente de riesgos instantáneos, hazard ratio, HR 2, 28, i.c. del 95% 1, 03-4, 93, P = 0, 042) conservó la significación estadística como variable independiente en el análisis multivariable. Conclusión: La NLR antes del tratamiento se asoció con respuesta patológica del OAC a la NAC y OS. Graphical Abstract: The neutrophil to lymphocyte ratio, dichotomized at 2·25, was strongly associated with Mandard tumour regression grade in patients who had neoadjuvant chemotherapy for oesophageal adenocarcinoma. The systemic inflammatory response may offer a novel therapeutic target for patients at risk of poor response. A simple tool to aid decision-making